2020
DOI: 10.48550/arxiv.2010.01717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STORIUM: A Dataset and Evaluation Platform for Machine-in-the-Loop Story Generation

Abstract: Systems for story generation are asked to produce plausible and enjoyable stories given an input context. This task is underspecified, as a vast number of diverse stories can originate from a single input. The large output space makes it difficult to build and evaluate story generation models, as (1) existing datasets lack rich enough contexts to meaningfully guide models, and (2) existing evaluations (both crowdsourced and automatic) are unreliable for assessing long-form creative text. To address these issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…While the tutorial will include our own work (Yao et al, 2019;He et al, 2019;Mittal et al, 2022;Goldfarb-Tarrant et al, 2020;Chakrabarty et al, 2020bAkoury et al, 2020;Stowe et al, 2021;Tian et al, 2021;Padmakumar and He, 2022;Chakrabarty et al, 2022a;Yang et al, 2022), we anticipate that roughly 40% of the tutorial content will be pulled from work by other researchers in NLP and machine learning communities include but not limited to (Ghazvininejad et al, 2016;Fan et al, 2018bFan et al, , 2019Van de Cruys, 2020;Riedl and Young, 2010;Lin and Riedl, 2021;Brahman and Chaturvedi, 2020;Mirowski et al, 2023;.…”
Section: Conclusion Future Directions and Discussion [25 Min]mentioning
confidence: 99%
“…While the tutorial will include our own work (Yao et al, 2019;He et al, 2019;Mittal et al, 2022;Goldfarb-Tarrant et al, 2020;Chakrabarty et al, 2020bAkoury et al, 2020;Stowe et al, 2021;Tian et al, 2021;Padmakumar and He, 2022;Chakrabarty et al, 2022a;Yang et al, 2022), we anticipate that roughly 40% of the tutorial content will be pulled from work by other researchers in NLP and machine learning communities include but not limited to (Ghazvininejad et al, 2016;Fan et al, 2018bFan et al, , 2019Van de Cruys, 2020;Riedl and Young, 2010;Lin and Riedl, 2021;Brahman and Chaturvedi, 2020;Mirowski et al, 2023;.…”
Section: Conclusion Future Directions and Discussion [25 Min]mentioning
confidence: 99%
“…Other methods generate stories by adapting higher-level attributes that can consist of goals and events as story units [62,72]. Akoury et al derive a large corpus of story components from STORIUM, an online collaborative game that lets users write stories based on cards as the framework [6]. With TaleStream, we leverage tropes from the wiki tvtrope.org as building blocks of stories.…”
Section: Related Work 21 Story Frameworkmentioning
confidence: 99%
“…The task of generating compelling story ideas is difficult to formulate and evaluate because it is inherently subjective. Our work focuses on ensuring coherence, a key characteristic that has been identified and extensively used in previous literature [6,7,19,67]. The suggested story ideas should fit seamlessly within the user's narrative, i.e.…”
Section: Trope Suggestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brahman et al [2020] focused on the task of interactive story generation, where the user provides mid-level sentence abstractions in the form of cue phrases to the model during the generation process. Akoury et al [2020] proposed another story generation system called STORIUM, where human authors query a model for suggested story continuations and edit them.…”
Section: Story Generationmentioning
confidence: 99%